Bariery rozwoju i funkcjonowania grup producenckich w polskim rolnictwie w świetle badań ankietowych - Grzelak, Aleksander (Barriers of Development and Running of Producer Groups in Polish Agriculture in the Light of the Questionnaire Researches, 2005)
The main aim of the article is analysis of barriers and conditioning activities of producer groups in agriculture in Poland. One has stated that there is a initial phase of development of producer groups in Poland. At the same time farms which are examined show not large inclination for this form of cooperation. The respondents pointed at main advantages resulting from membership to producer groups: factors connected with the improvement of competitive position on the market. Relatively clear characterization of farms taking part in the this process has been perceived. Besides that the hypothesis has been put forward that farms renting greater acreage do not display inclination of membership to producer groups because of higher costs of these farms activities and a scale of their production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 299-304